Capturing Street Soccer Game Performances and Workload During Homeless World Cup - Rizki Mulyawan; Sumaryanti; Sigit Nugroho (OVS LLC, 2023)
Study purpose. This study intended to convert the description of the strategies utilized in street soccer matches to international competitions. Materials and methods. Descriptive quantitative study was used that determined the participants by random sampling of the entire population. It acquired eight Indonesian national team athletes for the Homeless World Cup (HWC). The data was gathered from the six most important HWC matches, including those versus Zimbabwe, Israel, Romania, Brazil, Egypt, and the Netherlands, and examined using match footage. These six contests were chosen for their statistical analysis of decisive victories and defeats. Pearson Correlation was utilized for descriptive and inferential data analysis to evaluate the relationship between variables such as passing, shooting, goal, and goal allowed. Results. As indicated by the high association between passing and shooting accuracy and goal-scoring against the opponent's goal, passing and shooting were dominating throughout street soccer matches, especially during big events such as the HWC. Conclusions. This study may serve as a resource for all teams in the globe as they develop and implement training program plans to prepare street soccer teams in their various nations.